PENGGUNAAN SWAT DALAM PREDIKSI KETERSEDIAAN AIR UNTUK PENINGKATAN PRODUKTIVITAS PANGAN DI WILAYAH DAS WARSANSOM PAPUA BARAT - surahman, suryansyah; Sukri, Hadija; Setiawan, Eka Setiawan; Irwan, Irwan; Evar, Fitrawaty Orista; Hatimah, Husnul Hatimah; Prihatin, Prihatin; Putra, Ardi Manggala; Gustam, Andriyana; Aristyarini, Rizki; Hardina, Nur; Priyadi, Priyadi (Jurnal Eboni, 2024)
The availability of adequate water is one of the key factors in supporting increased food productivity, especially in areas that have large agricultural potential such as the Warsansom Watershed (DAS), West Papua. This research aims to predict water availability in the Warsansom watershed using the Soil and Water Assessment Tool (SWAT) model. The SWAT model was chosen because of its ability to simulate hydrological processes, erosion and land use dynamics in a spatial-temporal manner. The data used includes rainfall, temperature, topography, soil type and land use patterns. The analysis results show that the average annual rainfall is 322 mm/year, with an annual average temperature of 26.49°C. The Warsansom watershed area is dominated by secondary dryland forest (78.69%) which contributes significantly to groundwater infiltration and recharge. Regional delineation resulted in 33 sub-watersheds with a total area of ​​144,280 ha, as well as 273 hydrological response units (HRU) which became the basis for identifying critical areas in water management. SWAT simulations reveal potential risks of surface runoff in areas with steep slopes (36.53%) that require conservation interventions to reduce erosion and sedimentation. This research recommends data-based strategies for optimizing water resource management, including improving irrigation infrastructure, developing cropping patterns that are adaptive to water availability, and mitigating the impacts of climate change. By utilizing SWAT simulations, it is hoped that food productivity in the Warsansom watershed can increase sustainably, supporting food security in the West Papua region